PELAYANAN PUBLIK PADA KANTOR DESA PEBAUN HILIR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Ihza Mahendra; Geovani Meiwanda (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Village office services provide satisfaction for the community by completing services on time and supported by adequate human resources and infrastructure. The Pebaun Hilir Village Office has not fully provided satisfaction in public administration services for the village community This is due to inadequate infrastructure, especially the unavailability of a permanent village office, resulting in less than optimal service activities and most of them are carried out at employees' homes. This study aims to find out how the Public Service at the Pebaun Hilir Village Office, Kuantan Mudik District, Kuantan Singingi Regency. This research is descriptive qualitative by using secondary data collection techniques by conducting literature studies and secondary data sources as well as conducting direct research to the field to obtain primary data through observation, documentation, and interviews. In this study, researchers used the theory of Sitorus (2009; 86) which consists of 6 indicators namely Justice, Comfort, Care, Reliability, Convenience, and Trust. The results showed that the services of the Pebaun Hilir Village office in village government services had not been carried out optimally It is known that there is still a lack of provision of facilities and infrastructure supporting services such as the absence of a special waiting room for the applicant community, service reception counters and the provision of permanent village offices so that most service activities are carried out in the village. House. office employees, as well as the lack of employee cooperation in providing services so that service achievement is less than optimal.